2012
DOI: 10.1021/nl3004754
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Two-Dimensional Boron

Abstract: The structural stability and diversity of elemental boron layers are evaluated by treating them as pseudoalloy B(1-x)[hexagon](x), where [hexagon] is a vacancy in the close-packed triangular B lattice. This approach allows for an elegant use of the cluster expansion method in combination with first-principles density-functional theory calculations, leading to a thorough exploration of the configurational space. A finite range of compositions x is found where the ground-state energy is essentially independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

29
571
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 593 publications
(604 citation statements)
references
References 40 publications
29
571
0
4
Order By: Relevance
“…Recent works of Penev et al and Yu et al for 2D boron sheets showed that DFT calculations based on the PBE exchange-correlation functional find the absolute minimum of the cohesive energy vs. η convex hull to be at η = 1/8 = 0.125 and not at η = 1/9 = 0.11 (α-sheet). 34,35 As a bigger η value corresponds to a smaller surface density their results for 2D boron sheets and our results for 1D BNTs seem to indicate a similar trend. Interestingly, the cohesive energies of the transformed MTH-BNTs are found to vary over a sizable energy range of 75 meV/atom relative to the energy of perfect α-BNTs (see Figure 2).…”
Section: Resultssupporting
confidence: 84%
“…Recent works of Penev et al and Yu et al for 2D boron sheets showed that DFT calculations based on the PBE exchange-correlation functional find the absolute minimum of the cohesive energy vs. η convex hull to be at η = 1/8 = 0.125 and not at η = 1/9 = 0.11 (α-sheet). 34,35 As a bigger η value corresponds to a smaller surface density their results for 2D boron sheets and our results for 1D BNTs seem to indicate a similar trend. Interestingly, the cohesive energies of the transformed MTH-BNTs are found to vary over a sizable energy range of 75 meV/atom relative to the energy of perfect α-BNTs (see Figure 2).…”
Section: Resultssupporting
confidence: 84%
“…The existences, stability and electronic properties of these structures were already theoretically predicted before their experimental fabrication 27,28 . These new borophene structures, in accordance with the theoretical predictions, demonstrate metallic characters [25][26][27]29,30 and thus are good electric conductors, suitable as anode materials in rechargeable ion batteries. However, the real application of these 2D nanomembranes as an anode material in rechargeable ion batteries requires considerable amount of efforts.…”
supporting
confidence: 79%
“…Very recently, the 2D allotropes of boron (named as borophene), another neighbor of carbon in the periodic table elements, was also successfully synthesized on Ag(111) surface by two groups in parallel [14,15]. The experimentally observed borophene were found to consist of triangular boron grid and hexagonal holes, corresponding to  12 sheet and χ 3 sheet described by theoretical calculations [16][17][18][19], respectively. The fact that only a few structures were found on Ag(111) surface is surprising since freestanding borophene were predicted to be polymorphic with tremendous boron structures sharing competing binding energy near the global minimum [18].…”
mentioning
confidence: 99%